The Education and Lifestyle as Elements of Type 2 Diabetes Therapy - Przybyłek-Stępień, Zuzanna Adriana; Szustak, Jan; Bartosiński, Ryszard; Wijata, Michał; Wijata, Anna; Dutkiewicz, Justyna; Mączyńska, Wiktoria; Kąpa, Maria; Szepietowski, Bartosz; Kaźmierczak, Jakub; et al. (Quality in Sport, 2025)
Introduction Type 2 diabetes is the most common disorder of carbohydrate metabolism, characterized by high blood glucose levels. This disease has become one of the major global health issues. Treatment of type 2 diabetes involves both pharmacotherapy and lifestyle changes, with patient education playing a key role in the effectiveness of therapy. The goal of treatment is to prevent complications and improve the quality of life for patients. Aim of the Study The aim of this paper is to discuss the role of education and lifestyle in the therapy of type 2 diabetes. Materials and Methods This work was written based on a review of the current literature available through PubMed and other databases The following keywords were used for the literature review: “diabetes”, “epidemiology”, “complications”, “lifestyle”, and “education”. This allowed for an analysis of the pathogenesis, diagnosis, education, and lifestyle as elements of treatment, as well as complications associated with diabetes. Conclusions Type 2 diabetes is one of the most prevalent chronic diseases worldwide, with the incidence and prevalence continuously increasing. Early diagnosis and proper patient education are crucial in treatment, as they enable effective lifestyle modification, better disease management, and a reduction in the risk of complications. Diabetes education increases patient engagement in treatment, leading to better metabolic control and improved quality of life. In the future, further promotion of education will be important, as it will help in the earlier diagnosis of diabetes and reduce the number of its complications.